The Effect of Profitability And Financial Performance on Company Value with Corporate Social Responsibility as a Moderating Variable - Angeline Majesty Nugroho; Devina Setyawati (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2025)
This study aims to test profitability, financial performance has a positive effect on company value, and test corporate social responsibility has an impact on the influence of profitability on company value and corporate social responsibility has an impact on the influence of financial performance on company value. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 - 2021 with a total of 40 companies. The sampling technique was purposive sampling and a sample of 40 companies was obtained with 120 samples of observed data. The data analysis method used multiple linear regression analysis. Based on the results of data analysis and hypothesis testing, it can be concluded that the variables of profitability and corporate social responsibility in moderation of profitability have an effect on company value. While financial performance and corporate social responsibility in moderation of financial performance have no effect on company value.